Enhanced efficacy of aprepitant-based triple prophylaxis in preventing postoperative nausea and vomiting following metabolic bariatric surgery: a single-center, retrospective cohort study - Xiaodong Shan; Xiaodong Shan; Xiaodong Shan; Yidi Yang; Xiaoao Xiao; Mingchuang Zhang; Rui Chen; Qingqiu Huang; Yuanqing Gao; Xitai Sun; Xitai Sun (Frontiers in Medicine)
BackgroundMetabolic bariatric surgery (MBS) is associated with high risk of postoperative nausea and vomiting (PONV). We aimed to investigate the impact of aprepitant-based triple prophylaxis on PONV after MBS.MethodsWe reviewed a retrospective cohort of patients who underwent primary MBS between December 28, 2023 and May 31, 2024. The eligible patients were divided into two groups based on whether receiving additional oral single 125 mg dose of aprepitant preoperatively to the dual prophylaxis (ondansetron 8 mg and dexamethasone 10 mg). Multivariable and propensity score-adjusted analyses were performed to compare the composite PONV endpoints between the groups.ResultsA total of 207 patients were included in the study. Of these, 129 patients received dual prophylaxis, while the remaining 78 patients received additional single 125 mg dose of aprepitant. Similar to multivariable logistic regression analysis, propensity-adjusted logistic regression analysis revealed that the aprepitant-based triple prophylaxis group had a significantly higher complete response rate (82.1% vs. 24.0%, adjusted OR 10.312, 95% CI 4.186–25.399, p < 0.001), a lower incidence of PONV (59.0% vs. 85.3%, adjusted OR 0.287, 95% CI 0.125–0.663, p = 0.004), and required fewer rescue antiemetics (7.7% vs. 37.2%, adjusted OR 0.155, 95% CI 0.052–0.457, p < 0.001) compared to the dual prophylaxis group. Propensity score-adjusted analysis demonstrated that the addition of aprepitant to dual prophylaxis significantly reduced the incidence of PONV, vomiting frequency, and both the Nausea VAS and Nausea Subscale scores (all p < 0.05).ConclusionOur findings indicate that the addition of a single preoperative dose of aprepitant to a dual antiemetic prophylaxis of dexamethasone and ondansetron might be associated with a further improve outcomes related to composite PONV endpoints in patients undergoing metabolic bariatric surgery.